The prevalence and characteristics of overweight and obesity among students in Qatar. (July 2018) - Al-Thani, M.; Al-Thani, A.; Alyafei, S.; Al-Chetachi, W.; Khalifa, S.E.; Ahmed, A.; Ahmad, A.; Vinodson, B.; Akram, H.
Abstract: Objectives: To estimate the prevalence of overweight and obesity using World Health Organisation (WHO) cut-offs for the body mass index (BMI) among students of the general population living in Qatar in the period 2015–2016. Study design: Cross-sectional study. Methods: The study includes 164, 963 students aged 5–19 years. The body weight and height were measured to calculate the BMI. The WHO standard cut-offs were used to categorise the BMI into severe thinness (BMI z-score <−3), thinness (BMI z-score ≥−3 to <−2), normal (BMI z-score ≥−2 to <1), overweight (BMI z-score ≥+1 to <+2) and obese (BMI z-score >+2). Results: Overweight and obesity prevalence was 44.8% and 40.4% among males and females and 45.6% and 40.9% among Qatari and non-Qatari students, respectively. Odds of obesity and overweight status were significantly higher among 10–14 and 15–19 age groups than 5–9 years age group ( P < 0.001). By sex, males had 1.48 times higher odds of having obesity than females ( P < 0.001), and Qatari nationals had 1.4 times higher odds of obesity than non-Qataris ( P < 0.001). Although non-Qatari males also had higher odds of being overweight than females (odds ratio [OR] = 1.05, P = 0.0006), the opposite was seen among Qatari students (OR = 0.95, P = 0.01). Conclusion: The result of this survey provides evidence of a high prevalence of overweight and obese students living in Qatar. Therefore, preventive strategies are essential in this population to lower the incidence of being overweight and obesity. Highlights: Children and adolescents in Qatar are experiencing a high prevalence of overweight and obesity. Overweight/Obesity prevalence varies by population characteristics such as sex, nationality, and age. High body mass index is a major public health problem in Qatar. Multi-dimensional approaches could play critical role in the long-term reduction of obesity and related outcomes in the country.